2012
DOI: 10.7448/ias.15.2.17377
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing the risk of non‐vertical, non‐sexual HIV infection in children – beyond mother to child transmission

Abstract: After witnessing an episode of poor injection safety in large numbers of children in a rural under-resourced hospital in Uganda, we briefly review our own experience and that of others in investigating HIV infection in children considered unlikely to be through commonly identified routes such as vertical transmission, sexual abuse or blood transfusion. In the majority of cases, parents are HIV uninfected. The cumulative experience suggests that the problem is real, but with relatively low frequency. Vertical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Published data on the frequency and routes of horizontal HIV transmission to children is limited, although a few studies have reported the prevalence of horizontally acquired HIV in paediatric antiretroviral clinics at 1%, 5% (our clinic) and 4Á8% respectively (Vaz et al, 2010;van Kooten Niekerk et al, 2006;Reid and Van Niekerk, 2009). Despite growing evidence that horizontal HIV transmission to children is not uncommon (with four published studies in South Africa), there is no national registry to document this phenomenon and no advice on its prevention (Cotton et al, 2012;Shisana et al, 2008;Reid and Van Niekerk, 2009;Eley et al, 2003). Similar reports of healthcare-associated and communityacquired HIV transmission from elsewhere in Sub-Saharan Africa, India and Pakistan have been published, highlighting the need to create awareness of this global phenomenon and investigate the likely routes of transmission and identify risky practices (Vaz et al, 2010;Okinyi et al, 2009;Maniar, 2019;ProMED-mail, 2019;Mir et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Published data on the frequency and routes of horizontal HIV transmission to children is limited, although a few studies have reported the prevalence of horizontally acquired HIV in paediatric antiretroviral clinics at 1%, 5% (our clinic) and 4Á8% respectively (Vaz et al, 2010;van Kooten Niekerk et al, 2006;Reid and Van Niekerk, 2009). Despite growing evidence that horizontal HIV transmission to children is not uncommon (with four published studies in South Africa), there is no national registry to document this phenomenon and no advice on its prevention (Cotton et al, 2012;Shisana et al, 2008;Reid and Van Niekerk, 2009;Eley et al, 2003). Similar reports of healthcare-associated and communityacquired HIV transmission from elsewhere in Sub-Saharan Africa, India and Pakistan have been published, highlighting the need to create awareness of this global phenomenon and investigate the likely routes of transmission and identify risky practices (Vaz et al, 2010;Okinyi et al, 2009;Maniar, 2019;ProMED-mail, 2019;Mir et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…Vertical transmission of HIV, either in utero, intrapartum or post-natally through breastfeeding, is the predominant route for acquisition of HIV infection in children (Cotton et al, 2012). Since 2010, there has been an 18% decrease in the incidence of new HIV infections globally (Joint United Nations Programme on HIV/AIDS, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation